2005
DOI: 10.1128/jb.187.9.3110-3121.2005
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Lactococcal Prolate Phage-Phage Recombinants by an Enrichment Strategy Reveals Two Novel Host Range Determinants

Abstract: Virulent lactococcal prolate (or c2-like) phages are the second most common phage group that causes fermentation failure in the dairy industry. We have mapped two host range determinants in two lactococcal prolate phages, c2 and 923, for the host strains MG1363 and 112. Each phage replicates on only one of the two host strains: c2 on MG1363 and 923 on 112. Phage-phage recombinants that replicated on both strains were isolated by a new method that does not require direct selection but rather employs an enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…In view of this, we concluded that despite the resistance of L. lactis strain IL-1403 to c2 infection, initial phage binding to the cell surface was preserved, while the subsequent stage of phage development was blocked. A similar observation was reported for other c2-like bacteriophages (43). This result can be explained by the mechanisms of host cell infection by such phages.…”
Section: Discussionsupporting
confidence: 74%
“…In view of this, we concluded that despite the resistance of L. lactis strain IL-1403 to c2 infection, initial phage binding to the cell surface was preserved, while the subsequent stage of phage development was blocked. A similar observation was reported for other c2-like bacteriophages (43). This result can be explained by the mechanisms of host cell infection by such phages.…”
Section: Discussionsupporting
confidence: 74%
“…ORF26 shares similarity with several c2-like phage tail proteins, and the best match was with the tape measure protein (ORFl10) of phage c2 (34% identity; 193/ 567). Other matches included the industrial lactococcal phage isolates 5469 (35% identity; 180/507) and 5440 (28% identity; 148/528) (64). ORF26 was also found in the structure of Q54 as revealed by SDS-PAGE and mass spectrometry analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with the results of the lysogenic conversion assay, which verified that TP901-1C efficiently lysogenizes L. lactis UC509.9. Recently, it was reported by Rakonjac et al (40) that the acquirement of a new sequence adjacent to the cosR site in L. lactis phage c2 could overcome a host infection inhibition mechanism acting on the level of DNA injection or circularization by cos-end ligation. The corresponding pac site of TP901-1 is expected to be located in the vicinity of the late promoter (7), i.e., within the secondary recombination of TP901-1C.…”
Section: Discussionmentioning
confidence: 99%